Agro-industrial waste to biobutanol production: Eco-friendly biofuels for next generation. (October 2018) - Huzir, Nurhamieza Md; Aziz, Md Maniruzzaman A.; Ismail, S.B.; Abdullah, Bawadi; Mahmood, Nik Azmi Nik; Umor, N.A.; Syed Muhammad, Syed Anuar Faua'ad
Abstract: Biobutanol offers several merits that make it as top-tier fuels to be discovered. Due to energy and environmental concern, traditional biobutanol production using Acetone-Butanol-Ethanol (ABE) fermentation have been revamped. An important facet for biobutanol production is selection of feedstock as a substrate. Currently, lignocellulosic biomass has attracted much interest globally due to its sustainable supply and non competitiveness with food. Cellulosic biobutanol production can be generated by using lignocellulosic residue such as agricultural crops and residue. Moreover, finding efficient pretreatment is another vital parameter in biobutanol production process. This review will briefly update the recent trends for lignocellulosic biomass as a substrate and feasible pretreatment that can be used for production of biobutanol. Highlights: This review shows the important of biobutanol as a source of energy in the future. This review paper provide utilization of common and novel lignocellulosic biomass as a feedstock to produce biobutanol. This article evaluating the recent promising pretreatment used for biobutanol production.